Synthesis, characterization and anti-microbial studies of cadmium(II) compounds containing 3,10-C-meso-Me-8[14]ane(C). Crystal and molecular structure of cis-[CdLC(NO3)](NO3) - Roy, T.G.; Hazari, S.K.S.; Barua, K.K.; Anwar, N.; Zukerman-Schpector, J.; Tiekink, E.R.T. (Wiley-Blackwell, 2010)
One isomeric ligand, L-C, among three isomers of 3,10-C-meso-3,5,7,7,10,12,14,14-octamethyl-1,4,8,11-tetraazacyclotetrade canes (L-A, L-B and L-C, differing in the orientation of methyl groups on the chiral carbon atoms), on reaction with Cd(NO3)(2), CdCl2 and Cdl(2) producesoctahedral cis-mononitrato nitrate, trans-dichloro and trans-diiodo cadmium(II) compounds of formulae cis-[CdLC(NO3)](NO3), trans-[CdLCCl2] and trans-[CdLCI2], respectively. The cis octahedral compound undergoes substitution reactions with KSCN, NaClO4 and KBr to form the trans-substitution products, trans-[CdLC(NCS)(2)], trans-[CdLC(ClO4)(2)] and trans-[CdLCBr2], respectively, whereby the bidentate NO3- ligand is replaced by two monodentate ligands that occupy axial positions. All compounds were characterized on the basis of analytical, spectroscopic, conductometric and magnetochemical data. The crystal structure of cis-CdLC(NO3)](NO3) was determined by X-ray crystallography and showed the cadmium centre to exist within a cis-N4O2 donor set that defined a distorted octahedral geometry. Non-systematic variations in the Cd-O and Cd-N bond distances were correlated with significant hydrogen bonding interactions operating in the crystal structure. The latter interactions led to the formation of supramolecular two-dimensional arrays. The anti-fungal and anti-bacterial activities of these compounds were studied against some phytopathogenic fungi and bacteria. Coordination of L-C by cadmium resulted in more effective anti-microbial agents; no significant dependence upon the nature of the counter-ion was detected. Copyright (C) 2010 John Wiley & Sons, Ltd.